Survey of Nurse Practitioner Provider Knowledge, Barriers, and Current Practice in Referring High Risk Patients for Colorectal Cancer Screenings - Reardon, Lecia (My University, 2014)
Problem: Colorectal cancer (CRC) is the third leading cause of cancer and the second leading cause of cancer deaths in the United States (National Cancer Institute, 2014). Evidence supports preventive CRC screening, however, younger individuals at high-risk are often overlooked (Levin et al., 2008). Screening rates remain suboptimal despite these recommendations (American Cancer Society, 2013). Nurse practitioners (NP) can positively influence the incidence of high-risk screening referrals through knowledge and application of high-risk CRC screening guidelines. This knowledge when applied will transform high-risk CRC screenings from tertiary prevention, to primary and secondary prevention in CRC screenings and will improve health outcomes. Purpose: The purpose of this scholarly project was to evaluate NP knowledge of high-risk CRC screening guidelines, perceived barriers to CRC screening, and current NP screening practice patterns to inform decisions supporting a paradigm shift from tertiary prevention to primary and secondary preventive screening practices for those at high risk for CRC. Methods: A 16-question internet Qualtrics® survey was sent via email to 2155 NPs listed as primary care clinicians by the North Carolina Board of Nursing. Results: One hundred eighty respondents (8.3%) completed the survey, with 104 (57.5%) respondents rating themselves knowledgeable of high-risk CRC screening guidelines. The leading screening barriers identified were uninsured, patient refusal to do bowel prep; fear of finding cancer; and modesty concerns. The Chi Square test for independence of aggregate practice pattern questions demonstrated a statistically significant between self-perceived knowledge of high-risk CRC guidelines and actual high-risk CRC screening practices (Χ2= 4.1918, df = 1, p= .04). Conclusion: Over half (57.8 %) of the respondents reported knowledge of high-risk CRC guidelines with statistically significant relationship in aggregate practice patterns and perceived knowledge of guidelines. Reduction of public and clinician screening barriers using targeted interventions may improve health outcomes.
Keywords: High-risk cancer screening; Colorectal cancer screening; Colorectal cancer risk factors; Nurse practitioner cancer screening knowledge; Cancer screening barriers